2021
DOI: 10.1101/2021.11.11.468186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ab initio modelling of an essential mammalian protein: Transcription Termination Factor 1 (TTF1)

Abstract: Transcription Termination Factor 1 (TTF1) is an essential mammalian protein that regulates cellular transcription, replication fork arrest, DNA damage repair, chromatin remodelling etc. TTF1 interacts with numerous cellular proteins to regulate various cellular phenomena, and plays a crucial role in maintaining normal cellular physiology, dysregulation of which has been reported towards cancerous transformation of the cells. However, despite its key role in cellular physiology, the complete structure of human … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…Deconvolution of spectra collected from CD and Raman spectroscopy shows that TTF1 is a helical protein and this finding justifies its DNA binding activity. The above finding is in agreement with our computational model for full length TTF1 as well 16 . Previous literatures reporting protein DNA atomic structures have shown that the DNA is stabilized between the helices of those proteins 2,31 .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Deconvolution of spectra collected from CD and Raman spectroscopy shows that TTF1 is a helical protein and this finding justifies its DNA binding activity. The above finding is in agreement with our computational model for full length TTF1 as well 16 . Previous literatures reporting protein DNA atomic structures have shown that the DNA is stabilized between the helices of those proteins 2,31 .…”
Section: Resultssupporting
confidence: 92%
“…The secondary structure estimation after spectra deconvolution (as mentioned in material and methods) gave estimated percentage of α-helices (53.1%), β-sheets (6.4%) and random coils (40.4%) (Table 3), confirming predominantly the helical nature of the protein 28 . The above finding is in very much agreement with our computational abinitio study and simulation data of human TTF1 protein 16 . Raman spectroscopy is an important tool to study secondary structure of proteins and peptides.…”
Section: P U R Isupporting
confidence: 91%
See 2 more Smart Citations